Potential Protective Effects of Balakka Fruit Extract (Phyllanthus emblica L.) Against Doxorubicin-Induced Pancreatic Toxicity in Rats - Harahap, Viora Rezky; Ikhtiari, Refi; Ginting, Chrismis Novalinda; Raif, Martinus Ahmad (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The incidence of cancer is still high in the world, regionally and in Indonesia, where the incidence of new cases of breast cancer, uterine cervical cancer and lung cancer is the highest in Indonesia. The use of anthracycline doxorubicin as an anti-neoplastic agent is highly effective in various types of cancer in adults and children, including hematologic and solid tumors, but doxorubicin has serious organotoxicity, including pancreatic toxicity. The content of various compounds from Balakka fruit extract (Phyllanthus emblica L.) which has been identified through various studies, especially its potential as a pancreatic protective agent, through its antioxidant, anti-diabetic/hyperglycemic, and anti-hyperlipidemic activities. To determine the potential protective effect of ethanolic extract of Balakka fruit (Phyllanthus emblica L.) against doxorubicin-induced pancreatic toxicity in rats. This study used an experimental study with a completely randomized design to determine the potential protective effect of the ethanolic extract of Balakka fruit (Phyllanthus Emblica L.) against doxorubicin-induced pancreatic toxicity in rats (Rattus norvegicus). The results of qualitative phytochemical tests on the ethanolic extract of Balakka fruit contain alkaloids, flavonoids, phenols, steroids/triterpenoids, terpenoids and tannins. From the results of the different test results in the mean serial blood glucose levels more than 2 Kruskal Wallis groups, a significance value of p less than 0.05 was found, meaning that there were at least 2 groups that had a significant difference in fasting glucose levels (p = 0.003*) and TTGO test results at the 30th minute, 60th minute and 120th minute (p = 0.000*; p = 0.001*; p = 0.007*). The average fasting blood glucose levels of all treatment groups were in the normal range of 90 – 110 mg/dL. At the 120th minute of OGTT, it was found that the mean blood glucose level in the doxorubicin group reached 149.00 ± 7.99 mg/dL, still higher than the average level of the extract group, treatments 1 and 2 (p less than 0.05). And the mean blood glucose levels in the treatment groups 1 and 2 were significantly lower than the mean blood glucose levels in the doxorubicin group (p = 0.009*; p = 0.009*).The ethanolic extract of Balakka Phyllanthus Emblica L. fruit contains flavonoids, phenols, tannins, triterpenoids, terpenoids and alkaloids. Administration of ethanolic extract of Balakka fruit at a dose of 400 mg/kgBW can overcome pancreatic toxicity by maintaining a balance of glucose levels by decreasing blood glucose levels at the 30th minute, 60th minute, and 120th minute close to normal and can improve the pancreatic tissue of rats in a group of mice with doxorubicin-induced hepatotoxicity.